School Environment Assisted Inside Outside Circle Learning Model on Students’ Knowledge Competency of Science - Ayu Astari, Ni Made Dwi; Ardana, I Ketut (Jurnal Ilmiah Sekolah Dasar, 2020)
The low competency of students' science knowledge due to the lack of optimal model use in learning makes students difficult to understand learning. This study aimed to determine the effect of School Environment assisted Inside Outside Circle learning model on the science knowledge competency of the fourth-grade students. This study was a quasi-experimental study with a non-equivalent control group design. The population of this study was 275 students and the study sample were determined using random sampling techniques. Data collection was applied test method with instruments in the form of ordinary multiple-choice tests so the obtained data in the form of science competency values in the form of quantitative data were analyzed using t-test, namely polled variance. The results of the data calculation were t count = 6,599> t table = 2,000 at a significance level of 5% (dk = 30+ 31 - 2 = 59) then H0 was rejected and Ha was accepted, which means there is an influence of School Environment assisted Inside Outside Circle learning model on the science knowledge competency of the fourth grade students.